(untitled) (Papeles, 2017)
The purpose of this study is to shed clues on how the Colombian labor market promotes higher reading-writing skills by the undergraduates that finish their studies every year at Colombian universities. Thus, we turn to the Colombian National University looking to make a contrast between the undergraduate programs with a better performance at the standardized public tests, and those programs whose students experience a bigger welcome by the labor market once they finish their studies. Thereby, we find that, in spite of how crucial are reading-writing skills on an individual’s development, this is not as evident in the working world.